Protective effect of carvedilol on chenodeoxycholate induction of the permeability transition pore - Rolo, Anabela P. (2001)
Intracellular accumulation of toxic, hydrophobic bile acids has been proposed as one of the putative final common pathways leading to cholestatic liver injury. Furthermore, bile acids have been proposed as a causative factor for hepatic cardiomyopathy. Hepatic tissue concentrations of chenodeoxycholic acid (CDCA) during cholestasis are greater than those of other toxic bile acids. In the presence of calcium and phosphate, CDCA induced the permeability transition pore (PTP) in freshly isolated rat liver mitochondria. In this study, we evaluated the effects of carvedilol, a multirole cardioprotective compound, on CDCA-induced PTP. Mitochondrial membrane potential, osmotic swelling, and calcium fluxes were monitored. CDCA-induced PTP, characterized by membrane depolarization, release of matrix calcium, and osmotic swelling, was prevented by carvedilol. Under the same conditions, its hydroxylated analog BM-910228 did not reveal any protective effect. This finding reinforces carvedilol's therapeutic interest, because it may potentially prevent mitochondrial dysfunction associated with cardiomyopathy in the pathophysiology of cholestatic liver disease